Genetics, genotype stability analyses and evaluation of newly-developed high-yielding hybrid rice in multilocation - Sulaiman, Elixon Sunian @ Elixson (2021)
Hybrid rice varieties have been reported to produce 15-20% yield increment over the best conventional inbred varieties due to the heterosis or hybrid vigour. This yield advantage of hybrid rice can be a viable option to increase national rice production and farmers' income. Therefore, this study was conducted to develop locally adapted highyielding and stable hybrid rice for the Malaysian environment. The main objective of the study was to develop superior high-yielding and stable rice hybrids across environments for local cultivation. The study was divided into two main experiments; Experiment 1 was conducted to examine the combining ability effects of 120 F1 hybrids and 34 parents with the specific objectives were to develop and evaluate F1 hybrids derived from line × tester based on yield and growth performance, to estimate general and specific combining abilities of hybrid for yield, yield components and grain quality and to quantify heterosis values base on check varieties, mid-parents and better parents of the newly developed F1 hybrids. The experiment was conducted during off season 2016 (April – September) at MARDI Center of excellence for Rice Crop, Seberang Perai, Penang. Results of Experiment 1 showed that the top 20 hybrids that had significantly high mean yield which ranged from 46.62 to 54.46 g/plant as compared to the grand mean value (37.83 g/plant) were recorded in H17, H41, H35, H119, H108, H49, H105, H59, H94, H37, H107, H60, H43, H65, H27, H52, H46, H16, H3 and H2. These hybrids also showed the standard heterosis value was above 15% which is an important character for the selection of potential hybrids. Their grain characters were suitable to the Malaysian market which prefer rice with a long (> 6.21 mm length) and slender (> 3.00 mm of length to width ratio) grain, whereas the amylose content in the category of low (< 20%) to intermediate (20 – 25%). The combining ability was estimated where the rice testers T4 was a potential parent which had significantly positive GCA (general combining ability) effects mainly for yield (2.56), filled grains per panicle (4.25), total grains per panicle (4.37) and thousand grains weight (2.54). The best rice restorer line was L17 which recorded significantly positive GCA values particularly for yield (8.11), filled grains per panicle (12.57) and thousand grains weight (1.81). The SCA (specific combining ability) effect was estimated where hybrids H108, H65, H27, H114, H41, H35, H37, H81, H3, H105, H60, H2, H44, H17, H43, H118, H6, H49, H64 and H39 recorded significantly positive SCA values ranged from 4.84 - 15.05. Meanwhile, Experiment 2 was conducted to evaluate the G×E interaction effects and genotype stability of 20 selected hybrids which were tested in eight environments with a combination of four locations and two planting seasons. The specific objectives of Experiment 2 were to quantify the effect of environments on the expression of phenotypic values of the selected hybrid rice across different environments and to identify stable and high yield hybrid rice for commercial cultivation in Malaysia. Most of the evaluated quantitative traits were highly influenced by G×E (genotype × environment) interaction except for panicle length, grain length, grain width, milled grain length, milled grain width and milling recovery. Pooled data over environments revealed that eight hybrids; G19, G3, G18, G13, G8, G7, G14, and G12 recorded the highest mean yield (8.21, 8.10, 7.80, 7.49, 7.34, 7.24, 7.22 and 7.16 t/ha, respectively) as compared to the best check variety G21 (5.90 t/ha). The univariate and multivariate hybrid stability analyses for yield indicated that high yielding hybrids namely, G19, G3, G18, G8 and G14 had highly stable performance across the environments. The univariate hybrid stability and GGE (Genotype Main Effects + Genotype × Environment Interaction) biplot analysis revealed that hybrid G7 was highly stable performance across the environments, contrary in AMMI (Additive Main Effect and Multicative Interaction Effect) stability analysis found that this hybrid was unstable. Generally, there were three patterns of hybrid's interaction across the environments. The first categories are well-adapted across the environment (G19, G3, G18, and G8), the second categories are hybrid that is adapted to specific environments (G12) while, the third categories are the poorly adapted hybrids in all environments (G2, G4, G5 and G17) hence, these hybrids can be discarded. From this study, the newly developed hybrids rice, G19, G3, G18, H8 and G12 are recommended for local verification trial and upscaling before being released for cultivation in Malaysia.